Mobilisasi Dini pada Pasien Post Kraniotomi: Systematic Review - Azka Qothrunnadaa; Aqmarina Abidah; Yulmira Maria Tisel; Albertina Dete Tabik; Herdina Mariyanti; Harmayetty Harmayetty (Universitas Malahayati, 2026)
ABSTRACT Craniotomy is a neurosurgical procedure associated with postoperative complications such as infection and neurological decline due to immobilization. Early mobilization may accelerate recovery; however, its safety remains controversial, particularly in critically ill patients. This review aimed to analyze existing studies to determine the optimal timing for mobilization and its outcomes. A comprehensive literature search was conducted using descriptors and keywords in databases including Scopus, PubMed, ProQuest, Web of Science, and ScienceDirect. Study appraisal was carried out using the Joanna Briggs Institute (JBI) checklist. The included studies consisted of quasi-experimental designs, randomized controlled trials (RCTs), and non-experimental studies (prospective and retrospective) published between 2016 and 2025 in English. The search yielded 1,250 articles, of which 7 met the inclusion criteria and were reviewed. Early mobilization was initiated at 6, 12, 24, and 28–72 hours postoperatively, depending on patient tolerance. The studies involved patients undergoing general craniotomy procedures, including those for chronic subdural hematoma, aneurysms, and brain tumors. Outcomes assessed included length of stay (LOS), postoperative complications, and functional recovery. The findings suggest that initiating early mobilization within the first 24 hours—particularly within 12 hours—is an optimal strategy to reduce LOS, minimize complications, and accelerate functional improvement. Early mobilization typically progressed from head elevation, to sitting in a chair, standing unassisted, and walking, based on patient tolerance. Keywords: Early Mobilization, Post-Craniotomy. ABSTRAK Kraniotomi adalah prosedur bedah saraf dengan risiko komplikasi pascaoperasi seperti infeksi dan penurunan neurologis akibat imobilisasi. Mobilisasi dini dapat mempercepat pemulihan, tetapi keamanannya masih diperdebatkan, terutama pada pasien kritis. Review ini menganalisis studi-studi untuk menentukan waktu optimal mobilisasi dan dampaknya. Pencarian literatur dilakukan secara komprehensif menggunakan deskriptor dan kata kunci pada database Scopus, PubMed, Proquest, Web Of Science dan ScienceDirect. Appraisal studi menggunakan checklistdari Joanna Briggs Institute (JBI). Desain studi artikel yang disertakan meliputi quasy eksperiment, Randomized Control Trial (RCT), serta non eksperiemental study (prospektif dan studi retrospektif) yang diterbitkan pada tahun 2016-2025 dalam Bahasa Inggris. Pencarian menghasilkan sebanyak 1250 artikel, dan 7 artikel ditelaah dalam review ini. Mobilisasi dini dilakukan saat 6 jam pascaoperasi, 12 jam pascaoperasi, 24 jam pascaoperasi, dan 28-72 jam pascaoperasi sesuai dengan toleransi pasien. Karakteristik pasien yang terdapat pada artikel mencakup pasien yang menjalani kraniotomi umum termasuk untuk chronic subdural hematoma, aneurisma, dan tumor otak. Penelitian-penelitian tersebut juga mengobservasi length of stay (LOS), komplikasi postoperasi, dan fungsional. Hasil menunjukkan bahwa inisiasi mobilisasi dini dalam 24 jam pertama, terutama 12 jam, merupakan strategi optimal untuk memperpendek (LOS), meminimalkan komplikasi, dan mempercepat peningkatan pemulihan fungsional. Mobilisasi dini dimulai dari elevasi kepala, kemudian duduk di kursi, berdiri tanpa bantuan, dan berjalan sesuai toleransi pasien. Kata Kunci: Mobilisasi Dini, Post Kraniotomi.